Visual Prosthesis A Concise Guide - Weiss, Jeffrey N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
For the millions of people with untreatable blindness the thought of a visual prosthesis that would allow them to live a normal life has always been a distant hope. There have been intermittent bright spots that periodically fan that hope such as when Dr. Dobelle$1 (Bs visual prosthesis patient drove a car in an empty parking lot. This book will serve as an update of the work in developing a visual prosthesis. Chapters discuss the physiologic and engineering issues, alternative strategies, and patents, as well as recent research studies. Visual Prosthesis - A Concise Guide is a must-have resource for ophthalmologists, neurologists, engineers and physicists.s
Chapter 1. Blindness -- Chapter 2. Anatomy of the Visual System -- Chapter 3. History -- Chapter 4. Questions -- Chapter 5. Cortical Visual Prosthesis Studies -- Chapter 6. Retinal Implant Studies -- Chapter 7. Other Projects -- Chapter 8. Visual Prosthesis Patents -- Chapter 9. Noninvasive Brain Treatment Modalities -- Chapter 10. References. .
Keywords: Ophthalmology; Ophthalmology; Visual Prosthesis; Eye, Artificial; Blindness -- rehabilitation